APLIKASI SISTEM PAKAR BERBASIS WEB UNTUK MENDIAGNOSA PENYAKIT SYARAF PUSAT DENGAN METODE FORWARD CHAINING - Daniel Alexander Octavianus Turang (Lambung Mangkurat University, 2018)
The nervous system is one of the organs that perform activities of a coordinating body. Central nervous system functions primarily to detect, analyze, process and deliver information. Sensory systems collect information which are processed in the brain and transmitted to the motor system to control the movement, visceral activity, and endocrine functions. All the action from the sensory and motor systems are controlled by nerves which are interconnected to form a network of signaling. Lack of information and knowledge about neurological causes many sufferers of neurological diseases. The methods used in this research is a method of Forward Chaining. The system to be built is a computer-based information system by utilizing the technology of artificial intelligence that serves as system tools or the giver of neurological diagnosis results to the user. Diagnoses generated by this system is equipped with a type of central nervous disease with pecegahan and the way of treatment. The system will analyze your answers to each question are given, so that the obtained results diagnoses based on the existing knowledge base in expert system. Research results in the form of expert system that can help users know what kind of diseases of the central nervous, giving information regarding central nervous disease and knowing how treatment and prevention. Keywords: expert system, forward chaining, neurological diseasesSistem syaraf merupakan salah satu organ yang melakukan koordinasi kegiatan tubuh. Sistem syaraf pusat mempunyai fungsi utama untuk mendeteksi, menganalisa,mengolah dan menghantarkan informasi. Sistem sensorik mengumpulkan informasi yang akan diproses di otak dan diteruskan ke sistem motorik untuk mengontrol gerakan, aktivitas viseral, dan fungsi-fungsi endokrin. Semu aksi dari sistem sensorik dan motorik dikontrol oleh syaraf yang saling berhubungan membentuk jaringan signaling. Kurangnya informasi dan pengetahuan tentang penyakit syaraf menyebabkan banyak penderita penyakit syaraf. Metode yang digunakan dalam penelitian ini adalah metode Forward Chaining. Sistem yang akan dibangun merupakan suatu sistem informasi yang berbasis komputer dengan memanfaatkan teknologi kecerdasan buatan yang berfungsi sebagai sistem alat bantu atau pemberi hasil diagnosa penyakit syaraf kepada pengguna. Diagnosa yang dihasilkan oleh sistem ini dilengkapi dengan jenis penyakit syaraf pusat beserta pecegahan dan cara pengobatannya. Sistem akan menganalisa jawaban dari setiap pertanyaan yang diberikan, sehingga diperoleh hasil diagnosa berdasarkan basis pengetahuan yang ada dalam sistem pakar ini. Hasil penelitian berupa sistem pakar yang dapat membantu pengguna mengetahui jenis penyakit syaraf pusat, memberikan informasi mengenai penyakit syaraf pusat dan mengetahui cara pengobatan dan pencegahannya. Kata kunci: forward chaining, penyakit syaraf, sistem pakar